Effect of Maitland Mobilization Combined with Kendall Corrective Exercise on Pain and Postural Alignment of Patients with Upper Cross Syndrome: Pilot Study - Naeem Ullah; Fatima Amjad; Qamar Jan; Wagma Wajid; Aamir Niaz; Komal Hameed (American Journal of Physical Education and Health Science, 2026)
Upper Cross Syndrome (UCS) is a prevalent postural dysfunction resulting from muscle imbalances that causes forward head posture, rounded shoulders and thoracic kyphosis. Although manual therapy and corrective exercises are frequently performed, studies comparing the two have not been conducted extensively.To determine the feasibility and effectiveness of Maitland mobilizations alongside Kendall exercises in patients with UCS.A pilot single-blinded randomized controlled trial was performed involving 28 subjects (14 in each group). Group A was subjected to Maitland mobilizations alongside Kendall exercises, while Group B underwent only Kendall exercises for four weeks (three sessions/week). Pain, Craniovertebral angle (CVA), thoracic kyphosis and rounded shoulders were measured. Descriptive analysis and preliminary comparisons were made.Feasibility was established based on recruitment, retention rate (100%) and compliance (>90%). Both groups responded well, but group Had better responses. Group A had a higher pain reduction than Group B (-4.66 ± 0.82 versus -2.84 ± 0.75). Group A experienced significant improvement in CVA (+6.6°) than Group B (+2.7°).The combination of Maitland mobilization and Kendall exercises appears more effective than exercises alone in improving pain and postural alignment in UCS. Findings support feasibility and justify larger randomized controlled trials.